1981
DOI: 10.2307/3898128
|View full text |Cite
|
Sign up to set email alerts
|

Bison and Cattle Digestion of Forages from the Slave River Lowlands, Northwest Territories, Canada

Abstract: Dry matter disappearance (DMD) of native forages collected from the Slave River Lowlands (SRL), Northwest Territories, was consistently greater in bison (Bison bison) than in Hereford cattle (Bos taurus) when measured with a nylon bag technique. Overall average DMD values were 52% and 39% for bison and cattle, respectively. Mean percent DMD values for each plant species were: willow (Salk spp.), 56; slough sedge (Carex atherodes), 50; baltic rush (Juncus balticus), 47; aleppo avens (Geum aleppicum), 44; and no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

1986
1986
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 13 publications
0
12
0
Order By: Relevance
“…Some studies have suggested that bison have a superior ability to digest low-quality forages as compared to cattle (Peden et al, 1974; Richmond et al, 1977; Hawley et al, 1981a), but no studies have compared possible synergy between the two sources of inoculum. Hawley et al (1981b) observed that the in vivo digestion coefficients of DM, CP, aNDF and ADF from sedge hay were greater in bison than in Hereford steers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have suggested that bison have a superior ability to digest low-quality forages as compared to cattle (Peden et al, 1974; Richmond et al, 1977; Hawley et al, 1981a), but no studies have compared possible synergy between the two sources of inoculum. Hawley et al (1981b) observed that the in vivo digestion coefficients of DM, CP, aNDF and ADF from sedge hay were greater in bison than in Hereford steers.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have suggested that bison are more efficient than cattle at digesting poor-quality forages (Richmond et al, 1977; Hawley et al, 1981a,b). Proposed mechanisms for this heightened efficiency include a reduction in the rumen particulate passage rate, an increase in nitrogen (N) recycling, as well as differences in ruminal microbial populations (Hawley et al, 1981b).…”
Section: Introductionmentioning
confidence: 99%
“…Hironaka et al (1996) observed that pelleting reduced DM digestibility by 11% when chopped first-cut alfalfa was pelleted and the intake was 1.6 times maintenance. Hawley et al (1981) has suggested that the relatively high apparent digestibilities obtained with bison in some trials may be because they have an enhanced capacity to recycle nitrogen to their rumen. However, since the alfalfa contained 13.9% crude protein in this experiment, ruminal availability of N should not have been limiting.…”
Section: Digestibilitymentioning
confidence: 99%
“…Direct comparisons of digestibility found differences (Peden et al 1974;Hawley et al 1981;Schwartz and Ellis 1981) as well as no differences (Schaefer et al 1978;Plumb and Dodd 1993) between bison and cattle (including Hereford and Scottish Highland breeds). Digestion retention time was also greater in bison than cattle (Schaefer et al 1978).…”
mentioning
confidence: 94%
“…Similarities between bison and cattle and the adaptation of bison to rangelands of North America have led to many attempts to cross the two species and/or domesticate bison. Recent literature reviews have suggested that bison may be a more efficient range animal in North America because of their ability to digest low quality forage (Hawley et al 1981;Plumb and Dodd 1993), defend against predators (Carbyn et al 1993), survive harsh winter conditions, and have minimal calving difficulties (Haigh et al 2001). Sections below will indicate that many of these claims have not been supported by experimental comparisons between bison and cattle, and while testable, would be very difficult to evaluate under all potential situations.…”
mentioning
confidence: 99%